(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2016)
Isolation and characterization of Chlorella vulgaris (green alga) and Anabaena variabilis (cyanobacterium) were made from natural and artificial water bodies of Dhaka University and Khulna, Bangladesh from March through December 2014 using modified Chu-10D medium to determine their potential as feedstock for biofuel production. Optimum growth measured as total chlorophyll and optical density under varying physical and chemical environments was determined. The optimum growth for C. vulgaris was obtained at pH 6.5 under light intensity of 110 μE m-2 s-1 and one and a half times the concentration of the Chu-10D. Compared to this, the optimum growth for A. variabilis was obtained at 7.0 pH, 90 μE m-2 s-1 light intensity and normal Chu 10D. Both organisms were grown at 25o C temperature. Aeration of medium showed a significant positive growth for both the isolates. Supplementation of medium with vitamin B1, B6, B7 and B12 would yield higher biomass of C. vulgaris as biofuel feedstock. Vitamins were not required for growing A. variabilis. Asiat. Soc. Bangladesh, Sci. 42(2): 191-200, December 2016